Evaluating Industrial Products emotionally by Using Emojis: محمد علي حسين القيسي (Al-Academy, 2020)
Researches in the field of evaluation of industrial products emotionally are internationally new and non-existing in the Arabic speaking countries, which is considered the crux of the problem in the current research, in addition to the need of the designers and design students to know how to measure the emotional responses for the industrial product in order to get benefit from them in their designs. The research objective is to get a tool that uses emojis in measuring the emotional responses for the products. The researcher designed an emotional verbal wheel and emojis wheel. The sample of the research consisted of (7) chairs different in design and use, and the respondents were (89) students. The most important results are: 1- Designing the sensory emotional circuit by the use of emojis.2- Reaching at a sensory emotional description for the study samples